PEMANFAATAN PERASAN BELIMBING WULUH (Averrhoa bilimbi L) DALAM MENGHAMBAT PERTUMBUHAN ANGKA KUMAN PADA DAGING AYAM - Dyah Eka Kurniawati (LPPM Universitas Abdurrab, 2023)
Abstract Damage to meat can be caused due to physical impacts, chemical changes, and microbial activity. Four hours after cutting, without preservatives chicken meat begins to spoil. Star fruit plants have many benefits from leaves, fruits and even stems. The flavonoid content in star fruit works by damaging the cytoplasmic membrane so that bacteria will be damaged and die. The purpose of this study was to determine the squeeze of star fruit (Averrhoa bilimbi L) in inhibiting the growth of germ numbers in fresh cut chicken. This type of research is a pure experiment with pre and post test design with control. Researchers provide treatment or intervention on a variable. From this treatment, changes or influences on other variables are expected. The results of this study resulted in the average number of germs in 0, 2, 4, and 6-hour controls was 1.1 × 109 CFU / gr; 1.65 × 108 CFU/gr ; 1.69 × 108 CFU/gr ; 5.7 × 108 CFU/gr. While the average germ number in marinated chicken meat using variations in soaking time using star fruit juice with various variations in soaking time at 0, 2, 4, and 6 hours is 1.1 × 109 CFU / gr; 7.4 × 107 CFU/gr ; 8.5 ×108 CFU/gr ; 1.4 × 109 CFU/gr. So it can be concluded that star fruit juice has an effect on reducing the number of germs within 2 hours of treatment. © 20xx Universitas Abdurrab